2013
DOI: 10.1152/jn.00835.2012
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular mechanisms and neural strategies in the control of time-varying muscle contractions

Abstract: Erimaki S, Agapaki OM, Christakos CN. Neuromuscular mechanisms and neural strategies in the control of time-varying muscle contractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
2
3
1
Order By: Relevance
“…On average, maximum and minimum EMD were approximately 312 ms and 139 ms, respectively. In contrast to earlier findings, these values are greater than what is obtained with standard EMD computation [2], [3], [4], [5], but more similar to [11]. These differences may partly be explained by the methodology we employed to compute the MU/Force delay but also by the nature of the performed movement, as continuous time-varying movements differ in the way motor units are recruited.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…On average, maximum and minimum EMD were approximately 312 ms and 139 ms, respectively. In contrast to earlier findings, these values are greater than what is obtained with standard EMD computation [2], [3], [4], [5], but more similar to [11]. These differences may partly be explained by the methodology we employed to compute the MU/Force delay but also by the nature of the performed movement, as continuous time-varying movements differ in the way motor units are recruited.…”
Section: Resultscontrasting
confidence: 89%
“…This technique may achieve a more precise estimation of the portion of EMD due to MU recruitment while preserving the portion related to the mechanical properties of the muscle and the tendon. A similar approach was used previously [11] but was limited to the cross-correlation of the activity of only individual MUs with force. Conversely, here we estimate the neural drive as the cumulative set of discharges of several MUs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the accuracy of surface EMG decomposition is still debatable (Farina and Enoka, 2011; De Luca et al, 2015a), it is beyond the scope of the present setup to resolve pre-existing disputes over surface EMG decomposition. In the least, the motor unit behaviors during cyclic contraction observed in this study were largely consistent with those of previous reports (Iyer et al, 1994; Knight and Kamen, 2007; Erimaki et al, 2013). On the other hand, one technical merit of using surface EMG decomposition is that it can detect more active MUs than intramuscular EMG can, which helps to characterize error-dependent discharges in a small portion of the HP MUs.…”
Section: Discussionsupporting
confidence: 93%
“…Examinations of motor unit (MU) control have also revealed that the brain can mediate input excitation to motoneurons based on the perceived error and thereby maintain force at the target level via rate modulation and/or motor unit recruitment in various visual conditions (Kamen and Du, 1999; Contessa and De Luca, 2013). MUs discharge rhythmically during cyclic force-tracking (Iyer et al, 1994; Knight and Kamen, 2007; Erimaki et al, 2013). Fast cyclic force-tracking favors the use of predictive control, and MUs discharge more coherently at the target rate during faster force-tracking than during slower force-tracking (Sosnoff et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Again, it should be noted that all analyses are based on the temporal dynamics of the force produced by the participants and not on the displayed target. This renders any positive or negative tracking lags irrelevant [although they would be minimal given the highly feed-forward nature of this type of task (Erimaki et al, 2013 )]. To examine the relationship between tracking phase and force variability, we first converted each band-pass filtered force signal into an instantaneous amplitude signal by rectification and smoothing with a 200 ms Gaussian window.…”
Section: Methodsmentioning
confidence: 99%